Novel gels and films to mask boar taint in entire male pork. (June 2023) - Iniesta, Celia María; Garrido, María Dolores; Egea, Macarena; Linares, María Belén; Peñaranda, Irene
Abstract: Boar taint masking strategies were developed using hydrocolloids and spices to produce edible gels and films. Carrageenan (G1) and agar-agar (G2) were used for the gels and gelatin (F1) and alginate+maltodextrin (F2) for the films. The strategies were applied to both castrated (control) and entire male pork with high levels of androstenone and skatole. The samples were evaluated sensorially by a trained tasting panel through quantitative descriptive analysis (QDA). Lower hardness and chewiness of entire male pork, with high levels of boar taint compounds object of study, were found with the carrageenan gel, due to the better carrageenan gel adherence to the loin. The films showed that the gelatin strategy tended to have a certain "sweet" taste, and a higher overall masking than the alginate+maltodextrin film. In conclusion, a trained tasting panel found that gelatin film masked boar taint the most, followed by the alginate+maltodextrin film and the carrageenan-based gel. Highlights: The hydrocolloids used have been a suitable vehicle for the incorporation of spices. The spice mix used in the study masked the boar taint in both gels and films. The best masking strategy was gelatin film, followed by carrageenan gel. The use of these technological strategies can improve the marketing of entire male pork.